2022
DOI: 10.3389/fnagi.2022.1020699
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of dysregulated circular RNAs and construction of a ceRNA network involved in the pathology of Alzheimer’s disease in a 5 × FAD mouse model

Abstract: IntroductionAlzheimer’s disease (AD) causes a decline in cognitive function that poses a significant hazard to human health. However, the exact pathogenesis of AD and effective treatment have both proven elusive. Circular RNAs (circRNAs), which were initially deemed as meaningless non-coding RNAs, have been shown to participate in a variety of physiological and pathological processes. However, the variations and characteristics of circRNAs are not fairly well understood during the occurrence and development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Excessive mitochondrial fission promotes mitophagy through the PTEN-induced kinase 1 (PINK1)/Parkin-mediated mitophagy pathway, with a convergence of the miR-351-5p/MIRO2 axis in the pathology of AD (Chen et al, 2016). With the ongoing development of high-throughput sequencing and microarray technologies, many novel ncRNAs with regulatory roles in NDs are being identified (Cai et al, 2022b;Sun et al, 2022b;Zhao et al, 2022). For example, miR-455-3p is a newly discovered miRNA that showed significant upregulation in AD (Kumar et al, 2017), and its overexpression positively regulated the expression of mitochondrial biogenesis genes.…”
Section: Ncrnas Regulate Mitochondrial Gene Expressionmentioning
confidence: 99%
“…Excessive mitochondrial fission promotes mitophagy through the PTEN-induced kinase 1 (PINK1)/Parkin-mediated mitophagy pathway, with a convergence of the miR-351-5p/MIRO2 axis in the pathology of AD (Chen et al, 2016). With the ongoing development of high-throughput sequencing and microarray technologies, many novel ncRNAs with regulatory roles in NDs are being identified (Cai et al, 2022b;Sun et al, 2022b;Zhao et al, 2022). For example, miR-455-3p is a newly discovered miRNA that showed significant upregulation in AD (Kumar et al, 2017), and its overexpression positively regulated the expression of mitochondrial biogenesis genes.…”
Section: Ncrnas Regulate Mitochondrial Gene Expressionmentioning
confidence: 99%
“…ncRNAs are present at high concentrations in the CNS and show specific multidimensional expression, exerting immunomodulatory effects via direct or indirect interactions with various effector proteins or other molecules to form complex networks that regulate downstream immune response pathways ( 1 , 2 ). Next-generation sequencing has identified various ncRNAs dysregulated in CNS disorders, including long ncRNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) ( 3 – 5 ). Genome-wide association studies (GWAS) have also revealed numerous single nucleotide polymorphisms within lncRNAs and miRNAs ( 6 ), providing promising candidates for therapeutic targets or biomarkers for CNS disorders.…”
mentioning
confidence: 99%